The effect of work motivation, work discipline, and compensation on employee performance at PT X - Helliani Helliani; Alice Erni Husein (Trigin Publisher, 2025)
This study aims to examine the influence of work motivation, work discipline, and compensation on employee performance at PT X. Employing a quantitative research design based on the positivist paradigm, both primary and secondary data were utilized. Primary data were obtained through structured questionnaires distributed to employees, while secondary data were gathered from company archives and relevant literature. The research sample consisted of 80 respondents determined using the Krejcie and Morgan table. Data analysis was performed using multiple linear regression with the assistance of SPSS software to test the partial (t-test) and simultaneous (F-test) effects of the independent variables. The findings reveal that work motivation has a significant positive influence on employee performance, indicating that motivated employees tend to perform better. Similarly, work discipline shows a significant and positive impact on performance, suggesting that adherence to organizational rules and responsibilities enhances employee effectiveness. Compensation also demonstrates a significant positive effect, confirming that fair and adequate rewards strengthen employees’ productivity and commitment. Furthermore, simultaneous testing indicates that work motivation, work discipline, and compensation collectively exert a substantial influence on employee performance. Theoretically, these results reinforce previous empirical studies emphasizing motivation, discipline, and compensation as essential determinants of performance. Practically, the findings provide valuable insight for management at PT X in developing effective strategies to enhance employee motivation, enforce discipline, and implement fair compensation systems to improve overall organizational performance.